An alternative approach to realize all optical frequency encoded integrated AND-OR logic gate with control input using optical switches and its simulative verification - Ghosh, B; Halder, N; Roy, D; Hazra, S; Mukherjee, S; Sarkar, PP (International Journal of Computer Sciences and Engineering, 2025)
Optics has been recognizing as a good probable signal for realization of logic circuits, digital optical systems for optical communication and computation using optical switching devices for the utilization of super fast speed. Some optical logic gates can operate on the basis of frequency conversion process of some nonlinear materials. Semiconductor optical amplifier is recognized as a very promising and reliable optical device for implementing various all optical logical operations. Recently, more and more advanced technology should be needed to design compact and integrated version of devices. Here the authors have proposed an alternative approach to realize frequency encoded all optical integrated AND - OR logic gate with control input by which a single circuit operates on different logics using reflected semiconductor optical amplifier and add/drop multiplexer type optical switches. Again, this scheme of all optical frequency encoded integrated logic gate using optical switches with controlling input is successfully verified by proper simulation technique.